Utilization of Family Planning Services among Married Women of Reproductive Age in Bhimeshwor Municipality of Dolakha District (One Health Journal of Nepal, 2021)
Introduction: Family planning (FP) is an essential component to reduce; the maternal and neonatal mortality rate, and improve the child health, and also to achieve gender and economic equality. Recently, Nepal observed a setback in FP services utilization among Married Women of Reproductive Age (MWRA). Hence, we conducted a study to assess the FP services utilization among the MWRA of Bhimeshwor Municipality of Dolakha District of Bagmati ProvinceMethods: We conducted a cross-sectional descriptive study among 230 MWRA (15-49 years). Ethical approval was obtained from Nepal Health Research Council. Data collection tool included structured and semi-structured questionnaires. Data analysis was done on SPSS-version22. Categorical variables were described using numbers and percentages.Results: A total of 53.9% MWRA used different methods of FP. Depo Provera (42.7%) and Hormonal implants (0.8%) were the most commonly used and least common contraceptive method, respectively. Around one-third women who didn’t use any contraceptives responded the reason being fear of side effects (35.8%) and husband disapproval (29.2%). Almost two in three women (68.0%) who didn’t use any contraceptives had no intention of using it in the future.Conclusions: The utilization of FP services among MWRA is slightly more than half of the respondents. Though the utilization is considerably higher than the both national and provincial average but certainly will have to raise the bars to meet the standard set by Sustainable Development Goals (SDG). Furthermore, conduction of community programmes with an intention to sensitize about contraceptives and its possible effect would be beneficial.